Efforts to prevent and break the chain of the spread of Covid-19 in Universitas Muhammadiyah Magelang - Lintang Muliawanti; Muhammad Ridwan Sulistyono; Nalendra Bagas Adi Nugroho; Muhammad A Hanafi; Anisa Wahyuningtyas; Rindiyani Rindiyani (Community Empowerment, 2021)
The Covid-19 volunteer task force program at the Universitas Muhammadiyah Magelang (Unimma) aims to prevent and break the chain of the spread of COVID-19 in the campus environment. There are several methods, including screening, surveillance, as well as media publications and promotions. The results of the Unimma Covid-19 volunteer task force program obtained surveillance results with one suspect, three probable and no confirmed patients, close contact and discarded. In addition, the academic community at Unimma understands the importance of health protocols and is supported by the creation of poster materials posted on campus and social media Instagram and YouTube.